Spatial Distribution and Asymmetry of Surface Electromyography on Lumbar Muscles of Soldiers with Chronic Low Back Pain - Zengming Hao; Lin Xie; Jian Wang; Zhenhai Hou (Pain Research and Management)
This study investigated spatial distribution and asymmetry of surface electromyography on lumbar muscles during a sustained contraction in soldiers with and without chronic low back pain. Twenty healthy soldiers and twenty chronic low back pain (CLBP) soldiers had performed the Sorensen test with a duration of 60 seconds. The corresponding muscle fatigue, spatial distribution, and the asymmetry of muscle activity over bilateral paraspinal lumbar regions were measured by the high-density surface electromyography (HDsEMG). The paired and independent samples t-tests were performed to compare the degree of muscle fatigue and asymmetry. The repeated-measures analyses of variance (ANOVA) were used to compare spatial distribution between groups and muscle fatigue. The baseline characteristics of soldiers between groups were comparable. CLBP soldiers had significantly less muscle fatigue on both sides of erector spinae compared to healthy ones. The spatial distribution was significantly associated with the group factor but independent of muscle fatigue. In addition, the asymmetry of erector spinae activity in the CLBP soldiers was significantly higher than the healthy one. In conclusion, uneven spatial distribution and asymmetry of lumbar muscle activity play significant roles in CLBP patients. The HDsEMG could be used as an objective method in distinguishing the function of the erector spinae between healthy individuals and CLBP patients during 1 min sustained contraction.